Contribution of Leadership, Work Discipline, Work Motivation to the Performance of Experts of the Gerindra Faction of the House of Representatives of the Republic of Indonesia - Syarif, Sulfiani; Firman, Ahmad; Latief, Fitriani (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to analyze the contribution of leadership, work discipline, and work motivation to the performance of Gerindra Party Faction Experts within the House of Representatives of the Republic of Indonesia. The performance of experts is an important factor in supporting the implementation of the legislation, supervision, and budgeting functions of the House of Representatives, so effective human resource management is needed to improve the quality of this performance. This study uses a quantitative approach with a survey method. Data collection was conducted by distributing questionnaires to 86 experts from the Gerindra Faction of the House of Representatives of the Republic of Indonesia. The data analysis technique used was multiple linear regression analysis with the help of the Statistical Package for the Social Sciences (SPSS) program. Before the regression analysis was carried out, a validity, reliability, and classical assumption test was carried out. The results of the study show that leadership, work discipline, and work motivation partially or simultaneously contribute positively and significantly to the performance of the Experts of the Gerindra Faction of the House of Representatives. Among the three variables, leadership is the variable that has the most dominant contribution to the performance of experts. The results of this research are expected to be input for faction leaders in improving the performance of experts through strengthening leadership, work discipline, and work motivation.